2003
DOI: 10.1002/pds.841
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic drugs and fatal pulmonary embolism

Abstract: Our results for conventional antipsychotics are consistent with previous studies of non-fatal venous thromboembolism. The finding for antidepressants needs to be replicated in other studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 14 publications
(16 reference statements)
4
70
1
Order By: Relevance
“…The focus of the present analysis was on antidepressants, but we also found a significantly increased risk of VTE associated with use of other psychotropic drugs, which is consistent with findings from the previous reports that examined this association 7, 11, 12, 13, 29, 30…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The focus of the present analysis was on antidepressants, but we also found a significantly increased risk of VTE associated with use of other psychotropic drugs, which is consistent with findings from the previous reports that examined this association 7, 11, 12, 13, 29, 30…”
Section: Discussionsupporting
confidence: 91%
“…Of 5 studies with prospectively collected exposure information,7, 8, 9, 10, 11 a significant relationship between antidepressant use and VTE was reported in 3 (which was largely confined to users of tricyclic products)7, 8, 9 and the findings from one other was consistent with our findings, with wide CIs 11. The fifth study found no association,10 but the comparison group included patients taking thyroid replacement hormones, patients with a history of VTE or cancer were only excluded if diagnosed in the 36 months before cohort entry, follow‐up was not censored at cancer diagnosis or surgery, and no adjustment for body mass index, smoking, or physical activity was performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between conventional antipsychotics and VTE was investigated in 8 observational studies, listed in Table I [3][4][5][6][7][8][9][10] . Two studies suggest a positive association between conventional antipsychotics and VTE but are inconclusive (due to small numbers of patients) 3,8 .…”
Section: Psychotropic Drugsmentioning
confidence: 99%
“…5 7 Parkin et al used a New Zealand national death registry to identify adults under age 60 and without established risk factors and tracked deaths caused by pulmonary embolism between 1990 and 1998. 5 Zornberg and Jick defined cases as all venous thromboembolic events requiring hospitalisation for anticoagulation and drew participants from the UK general practice research database of three million patients. 7 None of the observational data can provide definitive evidence of a casual [causal?…”
Section: Asking a Questionmentioning
confidence: 99%